Directional change mediates the physiological response to high-intensity shuttle running in professional soccer players - Tang, R.; Murtagh, C.; Warrington, G.; Cable, T.; Morgan, O.; O`Boyle, A.; Burgess, D.; Morgans, R.; Drust, B. (Sports, 2018)
The purpose of this study was to investigate the influence that different frequencies of deceleration and acceleration actions had on the physiological demands in professional soccer players. Thirteen players were monitored via microelectromechanical devices during shuttle running protocols which involved one, three, or seven 180 degree directional changes. Heart rate exertion (HRE) (1.1 ± 0.7) and rating of perceived exertion (RPE) (5 ± 1) were significantly higher for the protocol which included seven directional changes when compared to the protocols which included one (HRE 0.5 ± 0.3, ES = 1.1, RPE 3 ± 0, ES = 2.7) or three (HRE 0.5 ± 0.2, ES = 1.1, RPE 3 ± 1, ES = 1.9) directional changes (p < 0.05). The gravitational force (g-force) as measured through accelerometry (ACC) also showed a similar trend when comparing the seven (8628.2 ± 1630.4 g) to the one (5888.6 ± 1159.1 g, ES = 1.9) or three (6526.9 ± 1257.6 g, ES = 1.4) directional change protocols (p < 0.05). The results of this study suggest that increasing the frequency of decelerations and accelerations at a high intensity running (HIR) speed alters the movement demands and elevates the physiological responses in professional players. This data has implications for the monitoring of physical performance and implementation of training drills.